1999
DOI: 10.1080/026505399103368
|View full text |Cite
|
Sign up to set email alerts
|

What's the problem? Who can help? The perspectives of children and young people on their well-being and on helping professionals

Abstract: This article reviews research evidence concerning the views of children and young people about the main problems and worries they experience and about the kinds of help they access and would like. The centrality of family and peers in both the generation and alleviation of dif® culties comes across strongly. Loss, bullying and family or peer con¯ict are among the main issues identi® ed by children. They appear to be much less concerned about matters that preoccupy many adults, such as drugs or abduction. Many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
7

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 21 publications
(23 reference statements)
2
43
0
7
Order By: Relevance
“…The top four responses were: bullying, home issues, school issues and risky behaviour. Similar findings were reported by Hill (1999) from research with both primary and secondary school children on factors that would evoke negative feelings in them and affect their well-being. It was found that family and peer relationship problems were the main causes of distress reported by the children and young people.…”
Section: Discussionsupporting
confidence: 87%
“…The top four responses were: bullying, home issues, school issues and risky behaviour. Similar findings were reported by Hill (1999) from research with both primary and secondary school children on factors that would evoke negative feelings in them and affect their well-being. It was found that family and peer relationship problems were the main causes of distress reported by the children and young people.…”
Section: Discussionsupporting
confidence: 87%
“…However, workers and working relationships are neither the only nor the most important resources in promoting desistance. Related studies of young people in trouble suggest that their own resources and social networks are often better at resolving their difficulties than professional staff (Hill, 1999). The potential of social networks is highlighted by 'resilience perspectives', which, in contrast with approaches that dwell on risks and/or needs, consider the 'protective factors and processes' involved in positive adaptation in spite of adversity.…”
Section: Supporting Desistancementioning
confidence: 99%
“…Here too, continuity and time are important (Shattall et al, 2007;Littauer et al, 2005;Hill, 1999). Positive outcomes have been shown to be associated with good client-helper relationships in a number of research studies and literature reviews (Lambert and Barly 2001;Horvath et al, 2011;Karver et al, 2006;Shirk and Carver, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Informality and friendliness are widely seen as being helpful (O'Brien, 1999;Philp et al, 2004;NECF, 2006;Shiner et al, 2004). Both adults and children want to feel heard and respected (Bedi, 2006;Ackerman and Hilsenworth, 2003;Horberg et al, 2004;de Winter and Noon, 2003;Hill, 1999;NECF, 2006). Young people with mental health problems share these values (Garcia et al, 2007).…”
Section: Discussionmentioning
confidence: 99%